Sources of Confusion in Infant Audiovisual Speech Perception Research - Shaw, Kathleen E.; Bortfeld, Heather (Frontiers in Psychology, 2015)
Speech is a multimodal stimulus, with information provided in both the auditory and visual modalities. The resulting audiovisual signal provides relatively stable, tightly correlated cues that support speech perception and processing in a range of contexts. Despite the clear relationship between spoken language and the moving mouth that produces it, there remains considerable disagreement over how sensitive early language learners — infants — are to whether and how sight and sound co-occur. Here we examine sources of this disagreement, with a focus on how comparisons of data obtained using different paradigms and different stimuli may serve to exacerbate misunderstanding.